Comparison of Scheimpflug tomography, Placido disc, and combined Placido Scheimpflug in the measurement of pupil offset in myopic population - Jiliang Ning; Jiliang Ning; Jiliang Ning; Jiliang Ning; Lijun Zhang; Lijun Zhang; Lijun Zhang; Lijun Zhang (Frontiers in Medicine)
IntroductionThis study aimed to compare the consistency of pupil offset measurements obtained using the Pentacam, Keratron Scout, and Sirius devices.MethodsThis retrospective cross-sectional study included 146 young myopic individuals (292 eyes) scheduled for refractive surgery at Dalian Third People’s Hospital between January 2023 and December 2023. Three devices were utilized to measure the chord mu of the pupil deviation along with the Cartesian distances of the X and Y coordinates (Px, Py) associated with the pupil offset. Repeated-measures analysis of variance was used to compare differences in pupil offset acquisition across various devices. Additionally, the intraclass correlation coefficient (ICC) and Bland–Altman plot were utilized to assess the consistency among the three devices.ResultsChord mu, measured using the Pentacam, Keratron Scout, and Sirius devices, were 0.18 ± 0.10, 0.21 ± 0.11, and 0.18 ± 0.11, respectively. The Px values were 0.00 ± 0.14, -0.02 ± 0.16, and -0.01 ± 0.13, respectively, while the Py values were 0.09 ± 0.13, 0.10 ± 0.15, and 0.10 ± 0.13. The ICCs for the three device measurements, chord mu, Px, and Py, were 0.817, 0.900, and 0.855, respectively. When comparing the three devices, the 95% limits of agreement (LoA) for mu and Px measured using the Sirius and Keratron Scout were the narrowest, ranging from −0.15 to 0.08 and −0.11 to 0.13, respectively. Additionally, the 95% LoA for Py measured using the Sirius and Pentacam was the narrowest, ranging from −0.13 to 0.15. The pupil centers in both eyes were predominantly located above the apex of the cornea.ConclusionSirius, Keratron Scout, and Pentacam have good consistency in pupil shift measurement in young myopic patients, and the three devices can be used as references in clinical practice.